The Application of Procurement Systems in IBS Housing Project - Ahmad, Abd Jalil; Mastura, Jaafar; Azlan Raofuddin, Nuruddin; Md Azree, Othuman Mydin (ExcelingTech Pub, UK, 2017)
Traditional procurement system has been critique due to inefficiency dealing with innovation and industry development. As the industry developed, modern and alternative procurement systems has been introduced such as Design and Built and Management fees. Malaysian National Housing Policy 2012 has focused on the implementation of industrialized building system (IBS) to transform the housing industry by improving its quality, more economical, speed to construct and less dependency on foreign labors. The success of these development will highly be depending on procurement system management. This paper explores the type of procurement system currently been used in the industry, the procurement system management and issues arise from the practice. The findings revealed that under the two most popular systems that are Traditional and Design and Built; there are no differences in terms of appointment of IBS Manufacturer where the IBS Manufacturer will be appointed late under the Main Contractor. Thus, it is hypothesized that the issues arise due to the practice of these 2 procurement system are almost similar which does not comprehend the need to cater innovation in the industry.